Functional and Practical Insights Into the Genetic Basis of Takayasu Arteritis - Desiré Casares‐Marfil; Amr H. Sawalha (ACR Open Rheumatology)
Takayasu arteritis (TAK) is a rare vasculitis characterized by inflammation of large arteries. Although the exact etiology of TAK remains unclear, a genetic predisposition to the disease has been established. Large‐scale genetic studies have significantly contributed to the identification of genetic variation associated with immune‐mediated diseases. To date, five genome‐wide association studies (GWAS) have been performed in TAK, identifying multiple genetic susceptibility loci across the genome. Here, we summarize the major findings from GWAS in TAK and provide an in silico functional evaluation of the associated loci (P < 5 × 10−8) and variants in high linkage disequilibrium with them (r2 > 0.8). By exploring gene expression and chromatin interaction data, we identified candidate causal genes in TAK, some of them with well‐known functional implications. The analysis of transcription factor motifs within TAK‐associated loci revealed enrichment of the STAT and RUNX families, both characterized by their role in immune functions and inflammatory responses. The enrichment in biological processes in susceptibility loci confirmed the involvement of specific immune‐related pathways in TAK. Further, we devised and calculated a cumulative genetic risk score for TAK and confirmed differences in genetic risk for the disease among ancestries. Finally, we provide a practical guide to communicate genetic information for TAK to patients and families.